(untitled) (CR. Conservación y Restauración, 2025)
One of the most representative aspects of heritage practices so far in the 21st century is the reclamation and repatriation of significant objects between States, territories, or cultural groups. This process has often been perceived as a necessary tool of decolonization in museums, having a certain degree of historical reparation but also of diplomatic instrument. This text attempts to explore the advantages and limits of this process, through some case studies from around the world. It will be seen how such processes create important precedents that by no means put an end to the struggles or political uses of heritage.